GEO-ECONOMIC FACTORS, PARENTAL INVOLVEMENT AND PROFICIENCY IN ENGLISH LANGUAGE AS DETERMINANTS OF PRIMARY SCHOOL PUPILS ACHIEVEMENT IN MATHEMATICS IN THE NIGER DELTA, NIGERIA (2014)
Mathematics and English Language are core subjects at the primary school level meant to develop numeracy and oral communication among pupils. Despite their importance, records show that pupils in the Niger Delta region usually score lower than their colleagues from other geopolitical zones in public examinations in these subjects. Researchers have tried to isolate the reasons for this gap in achievement. However little has been done on how geo-economic factors: environmental degradation (ED), poverty (PO), school location (SL); school attendance (SA), parental involvement (PI), and proficiency in English Language influence pupils' achievement in Mathematics. Therefore, this study examined the extent to which these factors influence primary school pupils' achievement in Mathematics in the Niger Delta region. The study adopted correlational design. Random sampling method was used to select 39 (rural = 23, urban = 16) primary schools from three states in the Niger Delta region: Delta (rural 10, urban 05), Bayelsa (rural 07, urban 06), and Rivers (rural 06, urban 05). One thousand and two hundred public primary six pupils and their parents (Rivers = 400, Delta = 400, Bayelsa = 400) participated in the study. Five instruments: Parents' Poverty Level Scale(r=0.73), Environmental Degradation Level Scale (r=0.81), Parental Involvement Scale (r=0.79), Pupils Mathematics Achievement Test (r = 0.71) and English Achievement Test (r=0.79) were developed by the researcher. Pupils school attendance scores were obtained from school records. Pearson correlation coefficients, path analysis and multiple regression were used for data analysis. The level of significance was set at 0.05. Mathematics achievement had positive significant relationships with environmental degradation (r=0.060) poverty (r=0.103), at-home involvement (r=0.139) and English language(r=0.295) while school location, at-school parental involvement and school attendance were not statistically significant. The fit statistics ?2(35, n = 1200) = 438.2, Root Mean Square Error of Approximation = 0.09, Comparative Fit Index = 0.59, Goodness of Fit Index = 0.93 showed that the hypothesised model moderately fit the observed correlations among the variables. Beta weights showed that ED (?=0.065), PO (?=0.082), At-home involvement (AHI) (?=0.169) and English language (ENG) (?=0.276) had direct and positive effects on Mathematics achievement. At-school parental involvement (ASI) (?= -0.96)had negative direct effect on Mathematics achievement. The ED (?=0.020), PO (?=0.029), ASI (?=0.074) and AHI (?=0.030) had positive and indirect effects on Mathematics. State (?=-0.008), SL (?=-0.02), SA (?=0.027) had only marginal indirect effects on Mathematics achievement. About 3% of the variance observed in Mathematics was accounted for by ED, PO, ASI, AHI, ENG, SA, SL and State. English language had the largest influence on Mathematics achievement, while at- school involvement had least influence. Geo-economic factors, parental involvement and proficiency in English Language had direct effects on Mathematics achievement. Therefore, pupils should be encouraged to improve on their use of English language as it enhances their understanding of Mathematics. Parents should be mobilized and their support enlisted in helping their children to succeed. Enforcement of stringent laws will reduce the devastation of the environment to provide conducive learning environment for primary school pupils.